HIV/AIDS and admission to intensive care units: A comparison of India, Brazil and South Africa - Kantharuben Naidoo; Jerome Amir Singh; Umesh Gangaram Lalloo (AOSIS, 2013)
In resource-constrained settings and in the context of HIV-infected patients requiring intensive care, value-laden decisions by critical care specialists are often made in the absence of explicit policies and guidelines. These are often based on individual practitioners' knowledge and experience, which may be subject to bias. We reviewed published information on legislation and practices related to intensive care unit (ICU) admission in India, Brazil and South Africa, to assess access to critical care services in the context of HIV. Each of these countries has legal instruments in place to provide their citizens with health services, but they differ in their provision of ICU care for HIV-infected persons. In Brazil, some ICUs have no admission criteria, and this decision vests solely on the 'availability, and the knowledge and the experience' of the most experienced ICU specialist at the institution. India has few regulatory mechanisms to ensure ICU care for critically ill patients including HIV-infected persons. SA has made concerted efforts towards non-discriminatory criteria for ICU admissions and, despite the shortage of ICU beds, HIV-infected patients have relatively greater access to this level of care than in other developing countries in Africa, such as Botswana. Policymakers and clinicians should devise explicit policy frameworks to govern ICU admissions in the context of HIV status. S Afr J HIV Med 2013;14(1):15-16. DOI:10.7196/SAJHIVMED.887